Is the Symbol Digit Modalities Test a useful outcome in secondary progressive multiple sclerosis?. (24th January 2021) - Koch, Marcus W.; Mostert, Jop; Repovic, Pavle; Bowen, James D.; Uitdehaag, Bernard; Cutter, Gary
Abstract: Background: It is unclear which cognitive outcome measure is the most useful for clinical trials in multiple sclerosis. To investigate the usefulness of the Symbol Digit Modalities Test (SDMT) as a clinical outcome measure in secondary progressive multiple sclerosis (SPMS), we describe the frequency of worsening and improvement events in a large randomized controlled trial (RCT) dataset. Methods: Using original trial data from the ASCEND trial ( n = 889), a recent large RCT in SPMS, we describe worsening and similarly defined improvement with and without 3‐month confirmation on the SDMT in the whole trial cohort and unconfirmed worsening and improvement on the Paced Auditory Serial Addition Test (PASAT) in a smaller subset ( n = 107). Results: Somewhat unexpectedly, SDMT scores steadily increased throughout the 2 years of follow‐up in this trial. There were overall few SDMT worsening events throughout the trial (generally fewer than 10% of participants), but improvement events steadily increased from around 50% of participants with improvement at 12 weeks to more than 70% at 84 weeks and beyond. PASAT scores followed a similar pattern. Conclusions: In this well‐characterized clinical trial cohort, the SDMT does not reflect the steady cognitive decline that patients with SPMS experience. Both SDMT and PASAT scores improve throughout follow‐up, possibly due to a practice effect. The SDMT may not be a useful outcome measure of disease progression in 2‐year clinical trials in SPMS. Abstract : Unexpectedly, Symbol Digit Modalities Test (SDMT) measurements steadily increased during follow‐up in a large clinical trial dataset, likely due to a practice effect. The SDMT does not reflect the steady cognitive decline that patients with secondary progressive multiple sclerosis (SPMS) often experience. The SDMT may not be a useful outcome in SPMS clinical trials.